Kualitas Indeks Tanah Sebagai Estimator dari Agroforestry Tanah Kesehatan di Tirtomoyo Sub-DAS, Wonogiri - Irfan Budi Pramono; Renita Ratna Prahesti (Agrosains : Jurnal Penelitian Agronomi, 2016)
Soil is a vital resource for humans and soil quality degradation will affect people's lives, either directly or indirectly. Tirtomoyo Sub-watershed decreas ed soil quality on lands. Vegetative methods by agroforestry systems has been done as conservation to prevent further soil quality degradation. The study aims to determine the condition and the correlation between indicators of physics, chemistry and biology as well as the health status of land agroforestry at Tirtomoyo Sub-watersheld using Soil Quality Index calculation. Descriptive exploratory res earc h through soil survey, soil sampling loc ations are determined by stratified random sampling method and obtained 11 locations. Data analysis that used includes the correlation analysis and PCA. The results showed that soil health in agroforestry land of Tirtomoyo Sub -watershed in a low state, with the most influential s oil quality indicators are Base Saturation (BS), total N, available P and Cation Exchange Capacity (CEC).